The Basic Principles of Satyam (Truth) Śivam (Godness) and Sundaram (Beauty) an Ideational Backround of Indian Aesthetic Contexts in Religious and Cultural Aspects. - Balakailasanathasarma, M. (South Eastern University of Sri Lanka, 2018)
The Indian theory of aesthetics inreligious and cultural aspects is deeply rooted in the triple-principal of Satyam (Truth), Sivam (Goodness / Auspiciousness) and Sundaram (Beauty). We believe that this phrase Satyam, Sivam, Sundaram express beautifully a special confluence of the devotional, the erotic - sensuous, and the real. 'Satyam' is the truth value;'Sivam' is the good value & 'Sundaram'is the beauty value. This study try to identify the concept of Satyam-Sivam-Sundaram, as a cornerstone of Indian Aesthetics contexts inreligious and cultural aspects.Indian aesthetics is a well-experimented psycho-analytical process of judgment. Indian logic postulates the perception of (i) The mundane (laukika), or perceptible by sense organs, and (ii) super sensuous (yaugika) or realizable introspectively. The classification of arts in Indian tradition is based on different aesthetic sensesin Religious and Cultural Aspects.Amongst the senses that lead to aesthetic experience are vision (dṛśya) and (Hearing-śravya). Architecture, sculpture and painting originate from vision, and music and poetry originate from hearing and theatre from the two together. Indian aesthetics have given birth to a distinct approach to Truth and Art. This phenomenon has prompted many scholars to commonly categorize the thought of Eastern cultures into the genre of "Oriental Thinking", the general essence of which is the spiritual understanding of Truth. But the emergence of what came to be termed as aesthetic and art appreciation during the modern age, in the west, and particularly during the 18th century, was an unprecedented development in the history of Indian aesthetics. During this period, ideationalbackgroundof aesthetics, that was in earlier times simply used as one of the paths of discovering reality, now comes to be applied subjectively and took on the external form of human emotion and creative expression. This fresh approach, in turn, gave rise to the emergence of new theories and the development of various styles of art in the Indian aesthetic contexts of religious and cultural aspects.
Keywords: Aesthetics; Aspects; Beauty; Culture; Religion